Identification of Vibrio Species and Total Vibrio Count in Kidney Tissue of Humpback Grouper (Cromileptes altivelis) Reared at Different Stocking Densities in Pond-Based Net Cages - Nafila Junia Azadia; Gunanti Mahasri; Abdul Manan (Airlangga University, 2026)
The humpback grouper (Cromileptes altivelis) is a high-demand grouper species, both domestically and internationally. However, the utilisation of this cultivation system still faces obstacles, especially in the field of disease. This research was conducted to determine the total Vibrio count (TVC) and identify Vibrio species in the kidney tissue of humpback grouper reared with different stocking densities in pond-based net cages. The TVC examination method was carried out using serial dilution and grown on selective TCBS media. Bacterial identification was carried out by observing colony colour, Gram staining, and biochemical tests (catalase, SIM, TSIA, OF, and MRVP test). The results show that the highest TVC value was obtained from high-density treatment (1.9 × 104 CFU/g), meanwhile, the lowest TVC value was obtained from normal-density treatment (0.1 × 101 CFU/g). The results of bacterial identification showed that 3 of the 5 isolates obtained during the study (V1, V2, V4) were similar to V. fluvialis, V. alginolyticus, and V. parahaemolyticus based on biochemical tests. This study concluded that Vibrio bacteria similar to V. fluvialis, V. alginolyticus, and V. parahaemolyticus were found in the kidneys of grouper fish cultured at different stocking densities in net cages, and that the TVC values remained within the normal range.